Parents' and health-care workers' understanding of wheeze in children: a systematic review. (November 2018) - Maskell, Katherine; Paudyal, Priyamvada
Abstract: Background: Parent-reported wheeze is often used as a proxy for childhood asthma. However, discordance in labelling of wheeze among parents and health-care workers (HCWs) affects true estimates of population wheeze. This systematic review aimed to summarise the evidence of parents' and HCWs' understanding of wheeze in children, and the relevant factors affecting this knowledge. Methods: A systematic literature search was performed to identify studies published in English from Jan 1, 1990, to Nov 16, 2017, in the following databases: Medline, Embase, CINAHL, BNI, Cochrane Library, and PsycINFO. Studies were eligible if they assessed parents' or HCWs' understanding (or both) of wheeze or definition of wheeze in children, or the association between parentally reported (unconfirmed) wheeze and HCW-confirmed wheeze. Non-English language studies were excluded. The methodological quality of the included articles was evaluated with Joanna Briggs Institute critical appraisal checklists. This analysis is registered with PROSPERO, number CRD42017076635. Findings: The initial search yielded 15 492 unique references, of which 21 met the inclusion criteria. The focus in nine studies was on parents, three focused on HCWs, and nine included both. Across studies, the mean percentage of parents correctly defining wheeze was 44·7% (SD 24·3; 95% CI 29·6–59·7), and the mean percentage correctly identifying it on video was 52·7% (12·8; 41·5–64·0). In one study, 97% of HCWs correctly defined wheeze, and, in another study, agreement between nurses and physicians in assessing wheeze severity was 52%. The mean percentage agreement between parent-reported wheeze and clinician-confirmed wheeze was 64·6% (15·4; 55·5–73·7). Parents' understanding of wheeze was affected by respiratory history in the parent or child, English as a first language, ethnicity, parental education, and method of ascertainment of symptoms. In HCWs, understanding was affected by their profession, age, and location. Interpretation: Parents' and HCWs' understanding of wheeze is inconsistent and is affected by parent-related, child-related, research-related, and HCW-related factors, with only moderate agreement between parent-reported and clinician-confirmed wheeze. These findings could have an important impact in epidemiological studies to estimate asthma prevalence, and in assessing respiratory symptoms in clinical practice. Funding: None.